A compact bit string accessibility map for secure XML query processing - Mirabi, Meghdad; Ibrahim, Hamidah; Udzir, Nur Izura; Mamat, Ali (Elsevier, 2012)
One of the challenging issues related to specifying a fine-grained access control on the XML data is how to implement the accessibility map in a compact format with minimum affect on the XML query processing. In this paper, we propose a Compact Bit String Accessibility Map (CBSAM) to implement the accessibility map in a compact format. In order to achieve a secure and efficient XML query processing, the CBSAM is integrated with the region number labeling scheme. The experimental results illustrate that the CBSAM compresses the accessibility map with minimum affect on the XML query processing when the access locality among the XML nodes is high.